Population genetic structure, genotypic and antigenic diversity of Theileria parva field strains from eastern and southern Africa - Sibeko-Matjila, K.P. (Kgomotso Penelope) (University of Pretoria, 2020)
Thesis (PhD)--University of Pretoria, 2019.